2010
DOI: 10.1017/s1074070800003941
|View full text |Cite
|
Sign up to set email alerts
|

Are Consumers Willing to Pay More for Biodegradable Containers Than for Plastic Ones? Evidence from Hypothetical Conjoint Analysis and Nonhypothetical Experimental Auctions

Abstract: This study used and compared hypothetical conjoint analysis and nonhypothetical experimental auctions to elicit floral customers' willingness to pay for biodegradable plant containers. The results of the study show that participants were willing to pay a price premium for biodegradable containers, but the premium is not the same for different types of containers. This article also shows the mixed ordered probit model generates more accurate results when analyzing the conjoint analysis Internet survey data than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
58
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 41 publications
7
58
2
Order By: Relevance
“…The presence of eco‐consumers has also been profitable to companies that appeal to them with a record of environmentally friendly or sustainable production practices (Russo & Fouts, ). Most research has found that many consumers are willing to pay a price premium for green products and certain segments share attitudes that are favorable to the environment (Laroche, Bergeron, & Barbaro‐Forleo, ; Straugh & Roberts, ; Yue et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of eco‐consumers has also been profitable to companies that appeal to them with a record of environmentally friendly or sustainable production practices (Russo & Fouts, ). Most research has found that many consumers are willing to pay a price premium for green products and certain segments share attitudes that are favorable to the environment (Laroche, Bergeron, & Barbaro‐Forleo, ; Straugh & Roberts, ; Yue et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…These “green” containers have emerged to take advantage of the green marketing and environmental awareness related to high fuel prices (Kale et al., ). Some studies have identified consumer segments with regard to their attitudes and behaviors related to recycling and preferences for plastic and plastic‐alternative biodegradable containers (Hall et al., ; Yue et al., ). Specifically, as the move to more eco‐friendly products continues, the value chain must examine not only product‐specific components, such as potting containers, but also the impact on consumers of production practices used to produce the product.…”
Section: Introductionmentioning
confidence: 99%
“…Findings by Barnes et al (2011) who assessed that consumers are willing to pay more for environmentally friendly food containers and Yue et al (2010) who measured a higher willingness to pay for biodegradable plant containers support this notion. Whereas these studies concentrated on non-durable packaging products, we found a strong correlation (r=.771) of the preference to buy environmentally-friendly durable consumer products and the willingness to pay more for environmentally friendly durable consumer products.…”
Section: Discussionmentioning
confidence: 95%
“…material proximity and origin, was found to make its sustainability claims more concrete and trigger higher pro-social experience (Magnier et al, 2017). Variation in the proximity and origin of materials embodied in products was tested in previous studies and it created discrepancies in user interest and preference (Kainz, 2016;Scherer, Emberger-klein, & Menrad, 2017;Yue et al, 2010).The material biography may also have an effect where the meaning of the original product is carried into the new product. For example, a jacket made from hot air balloon carries a 'freedom' feeling (Tseng Mu, 2013).…”
Section: Perception Of Sustainable Materialsmentioning
confidence: 99%